EFFECT of ADMINISTRATION of BAY LEAF EXTRACT (Eugenia polyantha) ON TOTAL CHOLESTEROL and TRIGLYCERIDE LEVEL S IN PATIENTS WITH HYPERTENSION and TYPE 2 DIABETES MELLITUS AT IMAN CLINIC MEDAN - Frisca Indriani Putri; Rahman, Shahrul (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2024)
Cholesterol is a fat component that stabilizes cell membranes and is a precursor of bile salts and steroid hormones. The HMG-CoA reductase enzyme has an important role in the cholesterol synthesis process. Triglycerides are the primary fats found in food that undergo emulsification in the small intestine by bile salts and are digested by lipase. The flavonoids in bay leaves will react with the hydroxyl groups in cholesterol. Saponins will increase the binding of cholesterol to fiber. Tannins can inhibit fat absorption in the intestine. This study examined the effect of administering bay leaf extract (Eugenia polyantha) on total cholesterol and triglyceride levels in patients with hypertension and Diabetes mellitus type 2 in Clinic Iman Medan. This research is a Quasi-experimental design using 32 samples consisting of 16 samples from the control group and 16 from the experimental group. This study used bay leaf extract in 200 mg bay leaf capsules with 3 doses given to each group. Based on the results of the hypothesis test using the Paired T-test and Wilcoxon test, giving bay leaf extract had no effect on total cholesterol and triglyceride levels with a P-value < 0.05. There was no effect of giving bay leaf extract (Eugenia polyantha) on total cholesterol and triglyceride levels in patients with hypertension and DM type 2